2016
DOI: 10.1111/jir.12332
|View full text |Cite
|
Sign up to set email alerts
|

Unsupportive parenting and internalising behaviour problems in children with or without intellectual disability

Abstract: Children with ID were found to be at higher risk of experiencing unsupportive, negative parenting than children with TD. Children of depressed fathers were especially vulnerable to developing internalising behaviour problems in an unsupportive parenting context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 57 publications
1
33
0
1
Order By: Relevance
“…The global increase in the population of children with ID living into adulthood who are now cared for at home has led to more fathers providing care for their children with ID (Caples et al, 2018;McKenzie, Milton, Smith, & Ouellette-Kuntz, 2016;Vacca, 2013;Willingham-Storr, 2014). Fathers are also caring for their children with complex health conditions requiring specific supports and interventions (Seliner, Latal, & Spirig, 2016), as well as for children presenting with significant behaviors that challenge (Rodas, Zeedyk, & Baker, 2016). There is a welldeveloped and established body of evidence regarding the impact of having a child with ID on families and siblings (Chadwick et al, 2013;Shin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The global increase in the population of children with ID living into adulthood who are now cared for at home has led to more fathers providing care for their children with ID (Caples et al, 2018;McKenzie, Milton, Smith, & Ouellette-Kuntz, 2016;Vacca, 2013;Willingham-Storr, 2014). Fathers are also caring for their children with complex health conditions requiring specific supports and interventions (Seliner, Latal, & Spirig, 2016), as well as for children presenting with significant behaviors that challenge (Rodas, Zeedyk, & Baker, 2016). There is a welldeveloped and established body of evidence regarding the impact of having a child with ID on families and siblings (Chadwick et al, 2013;Shin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that parents of children with IDs report more unsupportive reactions than parents of typically developing children (Jacobs, Mazzone, Simon, & Nader-Grosbois, 2019;Rodas, Chavira, & Baker, 2017;Rodas, Zeedyk, & Baker, 2016). These results were obtained by means of self-reported measures.…”
Section: Emotion-related Socialization Behaviors In Parents Of Childrmentioning
confidence: 85%
“…Fabes, Leonard, Kupanoff and Martin (2001) as well as Mirabile (2014) have observed that parents who report a high level of unsupportive reactions also express more negative emotions, and that these parents have children with poorer ER competences. It could also be interesting to include another measure of ERSBs, for example an observational measure, as Rodas et al (2016) did. Regarding conversations, new analyses could be applied by integrating data obtained using a new observational design and coding measure (currently undergoing valuation) for conversations about mental states between parents and children (Jacobs & Nader-Grosbois, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parents of children with ID have been found to display higher levels of intrusive and negative parenting behaviors when compared to parents of children with TD (Blacher, Baker, & Kaladjian, 2013;Brown, McIntyre, Crnic, Baker, & Blacher, 2011;Rodas, Zeedyk, & Baker, 2016).…”
Section: Parenting and Anxietymentioning
confidence: 99%